Wireless networks and security issues, challenges and research trends - Khan, Shafiullah; Khan Pathan, Al-sakib (Signals and communication technology, 2013)
This book provides broad coverage of wireless security issues including cryptographic coprocessors, encryption, authentication, key management, attacks and countermeasures, secure routing, intrusion detection, epidemics, security performance analysis and more.